Effect of preservation time on the quality of frozen semen in indigenous rams - Mahmuda, BBA; Nesa, Azizun; Zohara, BF; Alam, MGS; Bari, FY (Bangladesh Journal of Animal Science, 2015)
The study was carried out to observe the effects of preservation time on the quality of frozen semen of indigenous rams. Semen was collected using AV once a week from 4 rams. Tris based with 10% egg yolk and 7% glycerol extender was used to extend and freezing the semen. Fresh semen was evaluated for volume, density, mass motility and concentration, and mean values were observed as 0.8±0.2ml, 3.0±0.3, 3.2±0.7, 3.9±0.7×109/ml, respectively. Significant difference (p<0.05) was found for all the parameters among the rams. Mean values of motility, viability and normal morphology percentages were 83.3±4.3%, 88.2±4.4%, 84.2±3.5% in fresh semen while those of chilled semen at 40C were 74.7±2.3, 78.8±4.9 and 79.2±2.9%, respectively. For all the parameters, significant (p<0.05) difference was found among the rams. Frozen sperm motility was observed after thawing at 39-400C for 14-15 seconds. The mean motility, viability and normal morphology percentages after freezing for 24hrs, 7, 15 and 30 days of duration were 39.8±3.1, 41.1±4.3, 40.1±4.1 and 39.4±2.9%; 44.5±2.5, 45.3±2.8, 44.6±2.8 and 43.9±2.8%; 71.0±2.0, 71.7±1.5, 70.7±1.7 and 70.3±1.8%, respectively and values did not decrease significantly (p>0.05) with the increasing time of preservation. Non significantly decrease of the semen quality with advance of preservation time indicates the suitability of the protocol used for freezing of indigenous ram semen in Bangladesh. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23113 Bang. J. Anim. Sci. 2014. 44 (1): 10-15